2003
DOI: 10.1017/s0033583504003932
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion effects on ion channel gating

Abstract: Metal ions affect ion channels either by blocking the current or by modifying the gating. In the present review we analyse the effects on the gating of voltage-gated channels. We show that the effects can be understood in terms of three main mechanisms. Mechanism A assumes screening of fixed surface charges. Mechanism B assumes binding to fixed charges and an associated electrostatic modification of the voltage sensor. Mechanism C assumes binding and an associated non electrostatic modification of the gating. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 241 publications
(349 reference statements)
3
90
0
Order By: Relevance
“…We have previously identified charged residues that contribute to j out and to V 1/2 (13,15,48). However, we have not been able to completely transfer the effective surface charges from a metal-ion sensitive channel to a relatively metal ion-insensitive channel.…”
Section: Strontium Effects On Seven Wild-type Kv Channelsmentioning
confidence: 84%
See 4 more Smart Citations
“…We have previously identified charged residues that contribute to j out and to V 1/2 (13,15,48). However, we have not been able to completely transfer the effective surface charges from a metal-ion sensitive channel to a relatively metal ion-insensitive channel.…”
Section: Strontium Effects On Seven Wild-type Kv Channelsmentioning
confidence: 84%
“…Based on the model of Gouy and Chapman (26,27), the Grahame equation (28) describes the relation between surface charge and surface potential in terms of the ionic composition of the solution. Even though this equation is based on the simplistic assumption of smeared surface charges it has been shown that it rather well describes the surface potential of a plane with moderately spread out point charges (29) and thus that of most ion channels (15). Approximating the Grahame equation, as shown in the Appendix, we obtain the following:…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations